Time-window of offline long-term potentiation in anterior cingulate cortex during memory consolidation and recall - Junyu Liu; Akihiro Goto; Yasunori Hayashi (Neuroscience Research)
Episodic memories are initially formed in the hippocampus and subsequently transferred to cortical regions for long-term storage. This process, known as memory consolidation, involves plastic changes in synaptic transmission such as long-term potentiation (LTP). However, at what time points and specific locations LTP acts at remains unclear. We previously developed an optogenetic tool, cofilin-SuperNova (CFL-SN), that allows for the selective erasure of LTP within a limited time window. Using CFL-SN, here we show that the erasure of LTP in the anterior cingulate cortex (ACC) during sleep on the subsequent day, but not immediately following task acquisition, impairs recall of memory. However, allowing a single day without perturbation allowed memory to be recalled. Even after 7 days of repeated erasure of LTP, allowing LTP in the ACC on the 8th day restores memory recall. Once the memory is transferred, further LTP in the ACC is not necessary. Our findings indicates that the memory consolidation process completes in one sleep cycle and can occur at any timepoint up to 8th day.